UMP, HP and TEL formed a cooperation to groom more software experts - UMP, PNC
Universiti Malaysia Pahang (UMP) has established a cooperation with Hewlett-Packard (Malaysia) Sdn. Bhd. dan Technology Education Leader Sdn. Bhd. in a move to enhance its capability in producing competitive and marketable graduates.